2022
DOI: 10.1101/2022.04.25.489462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially-enhanced clusterwise inference for testing and localizing intermodal correspondence

Abstract: With the increasing availability of neuroimaging data from multiple modalities—each providing a different lens through which to study brain structure or function—new techniques for comparing, integrating, and interpreting information within and across modalities have emerged. Recent developments include hypothesis tests of associations between neuroimaging modalities, which can be used to determine the statistical significance of intermodal associations either throughout the entire brain or within anatomical s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Our results showed that it is necessary to use both cluster-wise enhancement and spatial autocorrelation modeling to increase sensitivity in testing variance components, which aligns with previous findings [12,13]. It was supported by comparing CLEAN-V to simpler methods: massive univariate analysis, CLEAN-V without spatial correlation, and CLEAN-V without cluster enhancement.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our results showed that it is necessary to use both cluster-wise enhancement and spatial autocorrelation modeling to increase sensitivity in testing variance components, which aligns with previous findings [12,13]. It was supported by comparing CLEAN-V to simpler methods: massive univariate analysis, CLEAN-V without spatial correlation, and CLEAN-V without cluster enhancement.…”
Section: Discussionsupporting
confidence: 88%
“…cortical thickness) where 'borrowing' information across spatial domains is expected to improve power. Also, a comprehensive exploratory analysis by Weinstein et al [13] reveals that applying exponential spatial autocorrelation function (SACF) is reasonable in many imaging modalities mapped onto the cortical surface. While applying the same assumption to volumetric (3D) imaging data could be questioned, we showed that a simplified version of CLEAN ('CLEAN-V without spatial correlation') also results in a dramatic increase in power and sensitivity compared to massive univariate analysis, which can be adopted easily.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations